Dotawo A Journal of Nubian Studies 2 - Gerven Oei, van (Punctum Books, 2015)
Dotawo: A Journal of Nubian Studies offers a multi-disciplinary, diachronic view of all aspects of Nubian civilization. It brings to Nubian studies a new approach to scholarly knowledge: an open-access collaboration with DigitalCommons@Fairfield, an institutional repository of Fairfield University in Connecticut, USA, and open-access publishing house punctum books. The first two volumes of Dotawo have their origins in a Nubian language panel organized by Angelika Jakobi within the Nilo-Saharan Linguistics Colloquium held at the University of Cologne, May 22 to 24, 2013. Since many invited participants from Sudan were unable to get visas due to the shutdown of the German Embassy in Khartoum at that time, the Fritz Thyssen Foundation funded the organization of a second venue of specialists on modern Nubian languages. This so-called "Nubian Panel 2" was hosted by the Institute of African & Asian Studies at the University of Khartoum on September 18 and 19, 2013. This volume publishes the proceedings of that panel. Future volumes will address three more themes: 1) Nubian women; 2) Nubian place names; 3) and know-how and techniques in ancient Sudan. The calls for papers for the first two volumes may be found on the back of this volume. The third volume is already in preparation with the assistance of Marc Maillot of the Section française de la direction des Antiquités du Soudan, Department of Archeology. We welcome proposals for additional themed volumes, and invite individual submissions on any topic relevant to Nubian studies.